Chemical Characterization and Sensory Relationships of Beef M. longissimus lumborum and M. gluteus medius Steaks After Retail Display in Various Packaging Environments - Jacqueline Ponce; J. C. Brooks; Jerrad F. Legako (Meat and Muscle Biology, 2020)
Volatile compounds, carbonyls, non-heme iron, and thiobarbituric acid reactive substances (TBARS) were measured in both raw and cooked beef samples to determine the effects of muscle and packaging type on beef flavor development. All paired strip loins and top sirloin butts were packaged under vacuum and aged for 14 d postmortem. After initial aging, all subprimals were fabricated to produce M. gluteus medius (GM) or M. longissimus lumborum (LL) steaks. At 14 d postmortem, steaks were randomly assigned to 1 of 5 package types: high-oxygen modified atmosphere lidded trays (80% O2/20% CO2 [“HIOX”]), carbon monoxide modified atmosphere lidded trays (0.4% CO/30% CO2/69.6% N2 [“CO”]), rollstock (forming and non-forming films [“ROLL”]), vacuum packaging without retail display (“VAC”), and traditional overwrap (“OW”) remained under vacuum prior to retail display. Steaks were stored in darkness an additional 7 d prior to display. At 21 d postmortem, HIOX, OW, CO, and ROLL packages were displayed for 48 h under continuous fluorescent lighting, while VAC steaks remained in dark storage. Packaging and muscle type impacted (P < 0.05) quantities of multiple volatile flavor compounds, including alcohols, n-aldehydes, esters, furans, hydrocarbons, sulfur-containing compounds,and ketones in both raw and cooked samples. Volatile compounds related to lipid oxidation were more (P < 0.05) prominent in HIOX packaging. Package type (P < 0.05) and muscle (P < 0.05) had an impact on raw-steak TBARS, although package type did not influence (P > 0.05) cooked-steak TBARS. The GM possessed greater (P < 0.05) TBARS values than the LL in both raw and cooked samples. Package type had no effect (P > 0.05) on carbonyl and non-heme iron content although these analyses differed among muscles (P < 0.05), with the GM being greater (P < 0.05) than the LL. These results indicate that the development of lipid oxidation that occurs during storage and display was muscle and packaging specific. Therefore, to maintain flavor, quality packaging systems should be selected on a muscle-specific basis.